Coal-based high-capacity sodium battery negative electrode material for energy storage and preparation method thereof
By using low-ash bituminous coal or anthracite combined with resin, a high-capacity sodium-electrode material is prepared, which solves the problem that the capacity and cost of the negative electrode material of sodium ion battery in the prior art cannot be taken into account, and capacity improvement and cost control are achieved.
Patent Information
- Application Number
- CN202411576684.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
AI Technical Summary
The existing sodium ion battery negative electrode materials are difficult to balance the increase in capacity and reduce costs, resulting in problems such as increasing energy density and cost control.
Low-ash bituminous coal or anthracite as the core material, combined with phenolic resin or epoxy resin, and spray granulation and high-temperature carbonization to form an integrated pore structure, and finally mixed with asphalt in proportion for high-temperature calcination to prepare a coal-based high-capacity Sodium-electrode material.
The capacity of sodium electro-negative electrode material has been effectively improved, from the original 250mAh/g to 330~350mAh/g, and the capacity has been increased by 32%~40%. At the same time, the spherical shape and tap density of the material have been improved, solving the cost and The problem of capacity cannot be taken into account.
Smart Images

Figure CN119390055A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials for energy storage batteries, and specifically relates to a coal-based high-capacity sodium battery negative electrode material for energy storage and a preparation method thereof. Background Art
[0002] Sodium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of sodium ions between the positive and negative electrodes to work, similar to the working principle of lithium-ion batteries. During the charging and discharging process, Na+ is embedded and extracted back and forth between the two electrodes: during charging, Na+ is extracted from the positive electrode and embedded in the negative electrode through the electrolyte; during discharging, the opposite is true. This process of sodium ions being embedded and extracted between the positive and negative electrodes realizes the charging and discharging of the battery.
[0003] Sodium ion battery positive electrode materials: mainly include layered oxides, Prussian blue analogs, etc. These materials have good sodium ion embedding / de-embedding properties and are the key to achieving high energy density in sodium ion batteries. Sodium ion battery negative electrode materials: commonly used are hard carbon, sodium titanate, etc. These materials have high specific capacity and good cycle stability, which can ensure that sodium ion batteries maintain stable performance during charging and discharging.
[0004] At present, sodium-ion batteries are increasingly recognized by the market as a cheap energy storage device. Improving the energy density and controlling the cost of sodium-ion batteries are still the challenges facing their industrialization. Improving the gram capacity of positive and negative electrode materials is the key to improving energy density and controlling costs.
[0005] Research on negative electrode materials for sodium ion batteries mainly focuses on the selection and preparation process of a single carbon source. Commonly used carbon sources include coal-based raw materials, biomass-based, asphalt coke, resins, etc. Sodium negative electrode materials prepared from coal-based materials have lower capacity and lower cost. Sodium negative electrode materials prepared from resins have higher capacity and higher corresponding cost. How to achieve low cost and high capacity of sodium negative electrode materials is an urgent problem to be solved. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a coal-based high-capacity sodium battery negative electrode material for energy storage and a preparation method thereof in view of the deficiencies in the above-mentioned prior art, so as to solve the technical problem that the capacity and cost of the current sodium ion battery negative electrode materials cannot be taken into account at the same time.
[0007] In order to achieve the above object, the present invention adopts the following technical solution: The present invention provides a method for preparing a coal-based high-capacity sodium negative electrode material for energy storage, comprising the following steps: S1, crushing the lump coal to micron level, and acid washing to obtain impurity-removed coal powder; S2, dissolving the resin in an organic solvent, adding impurity-removing coal powder, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry in S2 to obtain a precursor material; S4, subjecting the precursor obtained in step S3 to high-temperature carbonization treatment to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in proportion, and then calcining it at high temperature to obtain a mixture; S6. The mixed material after high-temperature calcination in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0008] A further improvement of the present invention is that in steps S1 and S2, the coal powder is low-ash bituminous coal or anthracite, the resin is phenolic resin or epoxy resin, and the mass ratio of the coal powder to the resin is 80-20:20-80.
[0009] A further improvement of the present invention is that in step S3, the mixed slurry is dried by spray granulation.
[0010] A further improvement of the present invention is that the temperature of the spray granulation is 110-200°C.
[0011] A further improvement of the present invention is that in step S4, the high temperature carbonization treatment includes a pre-curing treatment and a carbonization treatment, and the time is 1 to 3 hours.
[0012] A further improvement of the present invention is that the pre-curing temperature is 100-200°C and the carbonization temperature is 500-600°C.
[0013] A further improvement of the present invention is that in step S5, the mass ratio of carbonized material:asphalt is (5-20):1.
[0014] A further improvement of the present invention is that in step S6, the temperature of the high temperature calcination treatment is 1100-1500° C. and the time is 1-3 hours.
[0015] The present invention provides a coal-based high-capacity sodium negative electrode material for energy storage prepared by the preparation method.
[0016] A further improvement of the present invention is that the capacity is 330-350 mAh / g and the first efficiency is 88%-92%.
[0017] Compared with the prior art, the present invention has at least the following beneficial technical effects: The present invention provides a coal-based high-capacity sodium negative electrode material for energy storage and a preparation method thereof. By taking low-cost anthracite or low-ash coal as the core, introducing a resin carbon source, and adjusting the integrated pore structure, the capacity and first efficiency of the sodium negative electrode material are effectively improved, and the capacity of the sodium negative electrode material is increased from the original 250mAh / g to 330~350mAh / g, and the capacity is increased by 32%~40%. The material prepared by the invention has a high sphericity, which effectively improves the tap density of the material. The technical problem that the capacity and cost of the current sodium ion battery negative electrode material cannot be taken into account is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The structure diagram of the sodium negative electrode material prepared by the present invention; Figure 2 This is the electrochemical diagram of the sodium negative electrode material prepared by the present invention. DETAILED DESCRIPTION
[0019] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.
[0020] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0021] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.
[0022] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0023] Various structural schematic diagrams of the embodiments disclosed in the present invention are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.
[0024] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0025] The present invention provides a method for preparing a coal-based high-capacity sodium negative electrode material for energy storage, comprising the following steps: S1, crushing the lump coal to micron level, and acid washing to obtain impurity-removed coal powder; S2, dissolving the resin in an organic solvent, adding impurity-removing coal powder, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry in S2 to obtain a precursor material; S4, subjecting the precursor obtained in step S3 to high-temperature carbonization treatment to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in proportion, and then calcining it at high temperature to obtain a mixture; S6. The mixed material after high-temperature calcination in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0026] Among them, in steps S1 and S2, the coal powder is selected from low-ash bituminous coal or anthracite, the resin is selected from phenolic resin or epoxy resin, and the mass ratio of coal powder to resin is 80-20:20-80.
[0027] Among them, low-ash bituminous coal is a type of coal obtained by enrichment and fine washing in a coal washing plant. It has a high resistivity. Some selected bituminous coals have only a small amount of ash and impurities, and moderate volatile matter. The low ash content of low-ash bituminous coal is its remarkable feature, usually referring to coal with an ash content of less than 10%. Anthracite is the coal with the highest degree of coalification, commonly known as white coal or red coal. It has a high fixed carbon content, low volatile matter yield, high density, high hardness, high ignition point, and does not smoke when burning. Anthracite is black and hard, with a metallic luster, and a shell-like fracture. When burning, the flame is short and smokeless, and it does not coke. Generally, the carbon content is above 90%, and the volatile matter is below 10%.
[0028] Phenolic resin is originally a colorless or yellowish brown transparent substance. The products sold on the market often add colorants to present red, yellow, black, green, brown, blue and other colors. Phenolic resin is insoluble in water, but soluble in organic solvents such as acetone and alcohol. Phenolic resin is resistant to weak acids and weak bases, but will decompose when exposed to strong acids and corrode when exposed to strong bases. Epoxy resin refers to an organic polymer compound containing two or more epoxy groups in the molecule. Except for a few, their relative molecular mass is not high. The molecular structure of epoxy resin is characterized by the presence of active epoxy groups in the molecular chain. These epoxy groups can be located at the end, middle or in a ring structure of the molecular chain.
[0029] In step S3, the mixed slurry is dried by spray granulation, and the temperature of the spray granulation is 110-200°C.
[0030] In step S4, the high-temperature carbonization treatment includes a pre-curing treatment and a carbonization treatment, the time is 1-3 hours, the pre-curing temperature is 100-200°C, and the carbonization temperature is 500-600°C.
[0031] In step S5, the mass ratio of carbonized material to asphalt is (5-20):1.
[0032] In step S6, the high temperature calcination treatment is performed at a temperature of 1100-1500° C. and for a time of 1-3 hours.
[0033] Example 1 S1. crushing smokeless lump coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving phenolic resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 2:3, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 200° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 200° C. and then subjecting it to high-temperature carbonization treatment at 600° C. for 1 hour to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 20:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1500° C. for 3 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0034] Example 2 S1. crushing smokeless lump coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving phenolic resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 1:4, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 110° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 100° C. and then subjecting it to high-temperature carbonization treatment at 500° C. for 1 hour to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 5:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1100° C. for 1 hour in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0035] Example 3 S1. Grinding anthracite to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving the epoxy resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 3:2, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 150° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 200° C. and then subjecting it to high-temperature carbonization treatment at 600° C. for 2 hours to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 10:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1300° C. for 2 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0036] Example 4 S1. crushing low-ash coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving the epoxy resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 4:1, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 200° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 150° C. and then subjecting it to high-temperature carbonization treatment at 550° C. for 3 hours to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 15:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1300° C. for 2 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0037] Example 5 S1. crushing smokeless lump coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving the epoxy resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 3:2, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 160° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 200° C. and then subjecting it to high-temperature carbonization treatment at 600° C. for 1 hour to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 10:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1400° C. for 3 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0038] Example 6 S1. crushing smokeless lump coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving phenolic resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 2:3, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 200° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 200° C. and then subjecting it to high-temperature carbonization treatment at 600° C. for 1 hour to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 15:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1500° C. for 2 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0039] Example 7 S1. crushing smokeless lump coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving phenolic resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 1:4, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 110° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 100° C. and then subjecting it to high-temperature carbonization treatment at 500° C. for 1 hour to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 10:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1200° C. for 1 hour in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0040] Example 8 S1. Grinding anthracite to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving the epoxy resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 3:2, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 150° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 200° C. and then subjecting it to high-temperature carbonization treatment at 600° C. for 2 hours to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 12:1, and then performing high-temperature calcination treatment to obtain a mixture; S6. The mixed material calcined at 1500° C. for 2 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0041] Example 9 S1. crushing low-ash coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving the epoxy resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 4:1, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 200° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 150° C. and then subjecting it to high-temperature carbonization treatment at 550° C. for 3 hours to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 14:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1100° C. for 2 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0042] Example 10 S1. crushing smokeless lump coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving the epoxy resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 2:3, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 160° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 200° C. and then subjecting it to high-temperature carbonization treatment at 600° C. for 1 hour to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 15:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1400° C. for 2 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0043] Embodiment 11 S1. crushing low-ash coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving the epoxy resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 4:1, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 200° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 150° C. and then subjecting it to high-temperature carbonization treatment at 500° C. for 3 hours to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 10:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1000° C. for 3 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0044] Example 12 S1. crushing smokeless lump coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving the epoxy resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 3:2, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 160° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 200° C. and then subjecting it to high-temperature carbonization treatment at 600° C. for 1 hour to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 11:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1400° C. for 2 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0045] Embodiment 13 S1. crushing low-ash coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving the epoxy resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 3:2, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 150° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 180° C. and then subjecting it to high-temperature carbonization treatment at 600° C. for 1 hour to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 10:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1400° C. for 2 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0046] Embodiment 14 S1. crushing smokeless lump coal to micron level and acid washing to obtain impurity-removed coal powder; S2, dissolving phenolic resin in an organic solvent, and adding the above-mentioned impurity-removed coal powder in a mass ratio of 1:4, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry of S2 at 120° C. to obtain a precursor material; S4, pre-curing the precursor obtained in step S3 at 100° C. and then subjecting it to high-temperature carbonization treatment at 500° C. for 2 hours to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in a ratio of 13:1, and then calcining at high temperature to obtain a mixture; S6. The mixed material calcined at 1200° C. for 2 hours in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
[0047] Embodiment 15 like Figure 1 and Figure 2 As shown, the coal-based high-capacity sodium negative electrode material for energy storage prepared by the preparation method of the present invention has a capacity of 330-350 mAh / g and a first efficiency of 88%-92%.
[0048] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0049] In addition, it should be understood that although this specification is described in accordance with the implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. The above content is only to illustrate the technical idea of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution according to the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a coal-based high-capacity sodium negative electrode material for energy storage, characterized in that: The following steps are involved: S1, crushing the lump coal to micron level, and acid washing to obtain impurity-removed coal powder; S2, dissolving the resin in an organic solvent, adding impurity-removing coal powder, stirring and mixing evenly to obtain a mixed slurry; S3, drying the mixed slurry in S2 to obtain a precursor material; S4, subjecting the precursor obtained in step S3 to high-temperature carbonization treatment to obtain a carbonized material; S5, mixing the carbonized material obtained in step S4 with asphalt in proportion, and then calcining it at high temperature to obtain a mixture; S6. The mixed material after high-temperature calcination in step S5 is crushed and demagnetized to obtain a coal-based high-capacity sodium negative electrode material.
2. The method for preparing a coal-based high-capacity sodium negative electrode material for energy storage according to claim 1, characterized in that: In steps S1 and S2, the coal powder is low-ash bituminous coal or anthracite, the resin is phenolic resin or epoxy resin, and the mass ratio of the coal powder to the resin is 80-20:20-80.
3. The method for preparing a coal-based high-capacity sodium negative electrode material for energy storage according to claim 1, characterized in that: In step S3, the mixed slurry is dried by spray granulation.
4. The method for preparing a coal-based high-capacity sodium negative electrode material for energy storage according to claim 3, characterized in that: The temperature of spray granulation is 110~200℃.
5. The method for preparing a coal-based high-capacity sodium negative electrode material for energy storage according to claim 1, characterized in that: In step S4, the high temperature carbonization treatment includes a pre-curing treatment and a carbonization treatment, and the time is 1 to 3 hours.
6. The method for preparing a coal-based high-capacity sodium negative electrode material for energy storage according to claim 5, characterized in that: The pre-curing temperature is 100~200℃, and the carbonization temperature is 500~600℃.
7. The method for preparing a coal-based high-capacity sodium negative electrode material for energy storage according to claim 1, characterized in that: In step S5, the mass ratio of carbonized material to asphalt is (5-20):
1.
8. The method for preparing a coal-based high-capacity sodium negative electrode material for energy storage according to claim 1, characterized in that: In step S6, the high temperature calcination treatment is performed at a temperature of 1100-1500° C. and a time of 1-3 hours.
9. A coal-based high-capacity sodium negative electrode material for energy storage prepared by the preparation method according to any one of claims 1 to 8.
10. The high-capacity sodium negative electrode material for energy storage according to claim 9, characterized in that: The capacity is 330~350mAh / g, and the first efficiency is 88%~92%.
Citation Information
Patent Citations
Anthracite-based negative electrode material, sodium ion battery and preparation method of sodium ion battery
CN117317220A
High-capacity sodium battery negative electrode material for energy storage and preparation method of high-capacity sodium battery negative electrode material
CN117963886A